ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI - Suprihadi Suprihadi; Tria Oktaviana (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This study is a case study conducted at Pia AE Jaya Factory in Batu City, aiming to calculate the cost of production using the Activity-Based Costing (ABC) method and to analyze its differences from the traditional method. The background of this research lies in the fact that many small enterprises still apply the traditional method in allocating overhead costs, which relies on a single cost driver and often leads to cost distortions such as under costing or overcosting. This study employs a quantitative descriptive approach, with data obtained through observation and documentation. The cost drivers used in the ABC method include machine hours, number of setups, and number of production batches. The results show that the traditional method produces a lower cost of production compared to the ABC method because it only uses one cost driver. In contrast, the ABC method provides more accurate calculations by allocating costs based on activities and relevant cost drivers. Therefore, the ABC method helps the company determine a more precise cost of production and selling price, thereby maximizing profit.